2020
DOI: 10.17352/ijvsr.000054
|View full text |Cite
|
Sign up to set email alerts
|

The milk processing: Status, challenges and opportunities in ethiopia

Abstract: Livestock production in Ethiopia contributes about 16.5% of the national Gross Domestic Product (GDP), 35.6% of the agricultural GDP, 15% of export earnings, and 30% of agricultural employment. The performance of livestock product marketing was poor in the last decade, despite some improvement in recent years, especially in terms of aggressive policy and strategy on export of livestock and livestock products, indicating that the sector is still underexploited. There is need to promote the market-oriented produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…In South Ari district, 65% and 69% of households have experience selling raw milk and cheese; the rest 35% and 31% of respondents do not have the practice of selling it, respectively. Similar to this study Getabalew et al [45] noticed that in Ethiopia, fresh milk, butter, fermented whole milk (ergo), cottage cheese and buttermilk are sold through both formal and informal marketing channels. Regarding cheese marketing the current finding agreed with Tesfaye [46] who stated that household was not selling traditional cottage cheese (Ayib) in all the surveyed areas of Metema district rather it was consumed by the family members and given to calves and pet animals together with the whey (Aguat).…”
Section: Type Of Milk and Milk Product Marketingsupporting
confidence: 76%
“…In South Ari district, 65% and 69% of households have experience selling raw milk and cheese; the rest 35% and 31% of respondents do not have the practice of selling it, respectively. Similar to this study Getabalew et al [45] noticed that in Ethiopia, fresh milk, butter, fermented whole milk (ergo), cottage cheese and buttermilk are sold through both formal and informal marketing channels. Regarding cheese marketing the current finding agreed with Tesfaye [46] who stated that household was not selling traditional cottage cheese (Ayib) in all the surveyed areas of Metema district rather it was consumed by the family members and given to calves and pet animals together with the whey (Aguat).…”
Section: Type Of Milk and Milk Product Marketingsupporting
confidence: 76%
“…Wu et al [13] reported that sulfur supplementation decreased the methanogenic archaea population. Methanogens have a symbiotic association with protozoa by transferring hydrogen, thus decreasing methanogens reduced protozoa population [40]. Supplementation of sulfur in the dairy ration can be suggested to decrease methane emission by converting H 2 for methanogenesis to H 2 S [18,41].…”
Section: Ruminal Fermentation Characteristicsmentioning
confidence: 99%
“…The low level of pasteurized milk consumption in our study is likely associated with the under-developed milk pasteurization practice in Ethiopia which has resulted in that the vast majority (95%) of all milk produced in the country is sold through informal marketing systems without passing through pasteurization plants [53]. In such informal market systems, farmers often sell their milk directly to consumers and there is no mechanism for regulating bacteriological quality standards of the milk.…”
Section: Discussionmentioning
confidence: 91%